Pengaruh Promosi, Harga, Lokasi, Citra Destinasi dan Kualitas Layanan Terhadap Minat Berkunjung Di Pantai Karang Jahe Rembang - kamala, zubdatul; Sumastuti, Efriyani; Utami Puspitasari, Ratih Hesty (Universitas PGRI Semarang, 2024)
The purpose of the study carried out by researchers was to gain an understanding of how promotion, price, location, destination image and service quality influence the desire for tourists to visit Karang Jahe Rembang beach. Quantitative methods are used as a method in this research with descriptive research methods. Visiting interest (Y) is included in the dependent variable category, meanwhile promotion (X1), price (X2), location (X3), destination image (X4) and service quality (X5) are independent variables. The findings from this research identify that there are four variables that have a significant influence on the visiting interest variable in this research, namely price, location, destination image and service quality. Meanwhile, promotions do not have a significant impact on tourist interest in visiting. Based on the F test, simultaneous promotion, location price, destination image and service quality have an influence on interest in visiting tourism.